Geography : - English, Paul Ward (National Textbook Co., 1997)
The purpose of the book is to introduce college students to the breadth and spatial insights of the field of geography. The content is organized around the four major research traditions of the discipline: those of earth-science, culture-environment, location, and area analysis. Each of the four parts of the book centers on one of these geographic perspectives. Each of the first three parts contains chapters devoted to the subfields of geography. Thus, the study of weather and climate is part of the earth-science tradition; population geography is considered under the culture-environment tradition; and natural resources are included within the locational perspective. The tradition of area analysis (regional geography) is presented in a single final chapter, "The Regional Concept", that draws upon the preceding traditions and themes and is integrated with them by cross-references. Its case studies and examples illustrate the regional geographic application of the systematic themes developed by the earlier chapters. Although the organization provides a logical clustering of the subfields of the discipline, it is not an inflexible framework. Each chapter stands substantially alone. Each contains forward and back references to supporting material elsewhere in the book. Instructors can reorder the sequence of chapters to suit their preferences